Foresight: Pathogens from the permafrost. Combating the spread of an animal-borne disease with or without Russia - Michael Bayerlein; Miranda Böttcher; Bettina Rudloff; Pedro A. Villarreal (Stiftung Wissenschaft und Politik (SWP), 2024)
In the European summer of 2027, the world faces a threat, not only to human health but also to biological diversity and food security. An alarming scenario is emerging: The rapidly thawing permafrost in the Russian tundra has released an unknown form of anthrax that is primarily transmitted by birds. European efforts to collaborate with Russia in combating the spread of this pathogen are being met with resistance.
Keywords: 320; pathogens; permafrost; climate change; anthrax; Russia; global health; health threats; global health governance architecture